Development and Physical Stability Test of Salak Fruit Peel Extract Mouthwash as a Plaque Preventative - Nasrawati Basir; Nurfiddin Farid; Sriyanty Sadsyam; Andi Ulfiana Utari; Andi Bibit Utari Rahayu (The Indonesian Institute of Science and Technology Research, 2023)
The study aims to investigate the formulation and physical stability of salak peel extract mouthwash as a plaque preventer. Salak is a plant from Indonesia with medicinal properties, and its peel is a waste product that contains nutritional values such as protein, carbohydrates, water and low fat. The method used in this study is an experimental laboratory method. The salak peel was extracted through maceration of 96% ethanol and formulated into mouthwash with different concentrations of 5%, 10%, and 15%. The stability of the formulation was tested through organoleptic, pH, specific density, viscosity and clarity tests. The results showed no difference before and after the cycling test in organoleptic, pH, specific density, viscosity, and clarity tests, indicating the physical stability of the formulation.